FKM-Based Clustering Case Retrieval of the High-Rise Building Structural Intelligent Scheme Design - Liu, Shu Jun; Ou, Jin Ping; Zhang, Shi Zhong; Zhang, Shi Hai (Applied Mechanics and Materials, 2012)
Firstly, the disadvantage of the traditional "hard clustering" was analyzed; and the basic principles and algorithm steps of the fuzzy clustering was presented, it can express and process the class of objects which is not clearly in nature. Secondly, the theory and cluster analysis method is introduced to design high-rise structure; based on the fuzzy K-Means clustering analysis, the case retrieval method of the high-level structural intelligent design was established. Lastly, the example of engineering application was given in where the 26 projects data was used as the basis for the cluster and instance retrieval; the former 20 data is used to cluster and the last 4 data used to instance retrieval, the clustering member is k=4. Practice shows that the fuzzy k-means cluster analysis method is effective for the intelligent design of high-rise structure to obtain an instance, and opens up new ways and means for the high-rise building intelligent design.